2021
DOI: 10.2106/jbjs.20.00569
|View full text |Cite
|
Sign up to set email alerts
|

Venous Tumor Thrombus in Primary Bone Sarcomas in the Pelvis

Abstract: Background:Few investigations of venous tumor thrombus (VTT) in primary pelvic bone sarcomas are available. We aimed to identify the prevalence, associated factors, and prognosis of VTT across different types of pelvic sarcomas and to propose an algorithm for management.Methods:We included 451 consecutive cases of primary, bone-derived, treatment-naive, pelvic sarcomas in this study. Demographic data and the results of initial laboratory tests, imaging examinations, and oncological evaluations were extracted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…While poorly quantified, the available clinical data suggest that this phenomenon carries a poor prognosis for the patient. 23…”
Section: General Considerationsmentioning
confidence: 99%
“…While poorly quantified, the available clinical data suggest that this phenomenon carries a poor prognosis for the patient. 23…”
Section: General Considerationsmentioning
confidence: 99%
“…A few studies have identified risk factors for poorer oncologic and surgical outcomes in pelvic tumors. These include a venous tumor thrombus, a margin of <2 mm, complete acetabular resection compared with transacetabular resection, and sarcopenia 1,3,7,8 .…”
Section: Pelvis and Spinementioning
confidence: 99%
“…A few studies have identified risk factors for poorer oncologic and surgical outcomes in pelvic tumors. These include a venous tumor thrombus, a margin of <2 mm, complete acetabular resection compared with transacetabular resection, and sarcopenia 1,3,7,8 .The National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) database, the American College of Surgeons (ACS) National Cancer Database, and the California Cancer Registry were queried by several authors who concluded that radiation therapy is the most common local modality used in the United States for Ewing sarcoma of the sacrum or pelvis and has similar efficacy to surgical resection with or without radiation therapy; that 5-year disease-specific survival in patients with mobile vertebral column sarcomas was 56%, with worse survival for osteosarcoma; and that patients with malignancies of the mobile spine with public insurance are vulnerable to worse outcomes, even if they receive standard treatment 6,9,11 .Disclosure: The Disclosure of Potential Conflicts of Interest forms are provided with the online version of the article (http://links.lww.com/JBJS/H270).…”
mentioning
confidence: 99%
“…However, nearly 20% of OS patients are found to have metastasis at diagnosis, with a poor prognosis due to insensitivity to standard therapy [ 2 , 5 , 6 ]. One aggressive characteristic of primary OS is its tendency to intravasate into the adjacent veins and generate a metastatic tumor thrombus (almost 23% patients of with primary pelvic OS were found to have tumor thrombus), which could be exploited as a special study model for the early stage of tumor metastasis [ 7 ]. The occurrence of tumor thrombus substantially increases the rate of metastasis in many tumor types including osteosarcoma, renal cell carcinoma, and hepatocellular carcinoma [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…One aggressive characteristic of primary OS is its tendency to intravasate into the adjacent veins and generate a metastatic tumor thrombus (almost 23% patients of with primary pelvic OS were found to have tumor thrombus), which could be exploited as a special study model for the early stage of tumor metastasis [ 7 ]. The occurrence of tumor thrombus substantially increases the rate of metastasis in many tumor types including osteosarcoma, renal cell carcinoma, and hepatocellular carcinoma [ 7 9 ]. Patients with tumor thrombus in OS generally had a worse prognosis due to early distant metastasis and high local recurrence risk since scraps of tumor thrombus could skip across the reactive zone encapsulating the tumor and metastasize to distant organs early in the disease process [ 7 ].…”
Section: Introductionmentioning
confidence: 99%